Profundización teórica de modelos de volatilidad ARCH - GARCH y una aplicación al caso colombiano (2009)
ThisworkpresentsthetheoreticalsupportofARCHandGARCHmodelsproposed by Engle (1982) and Bollerslev (1986), developing the demonstrations of mean and variance, conditional and non-conditional based in the assumptions made by Engle (1982) and ﬁnally it presents an adjustment process, which presents the dynamic proper of ARCH and GARCH models.